Adhesive composition, adhesive, adhesive sheet and laminate
Patent Information
- Application Number
- JP2022519904
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-07
- Filing Date
- 2021-03-19
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2041-03-19
AI Technical Summary
【0026】 本発明に係る粘着性組成物、粘着剤、粘着シートおよび積層体は、段差追従性に優れるとともに、光学ムラの発生を抑制することができる。
Smart Images

Figure 0007645251000016 
Figure 0007645251000017 
Figure 0007645251000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition, an adhesive, an adhesive sheet and a laminate suitable for use in displays and the like. [Background technology]
[0002] In recent years, various mobile electronic devices such as smartphones and tablet terminals are equipped with displays that use display modules having liquid crystal elements, light-emitting diodes (LED elements), organic electroluminescence (OLED) elements, etc., and these displays are often touch panels.
[0003] In such displays, a protective panel is usually provided on the front side of the display module. As electronic devices become thinner and lighter, the protective panel is being changed from the conventional glass plate to a plastic plate such as an acrylic plate or a polycarbonate plate.
[0004] Here, a gap is provided between the protective panel and the display module so that even when the protective panel is deformed by an external force, the deformed protective panel will not collide with the display module.
[0005] However, when such a gap, i.e., an air layer, is present, there is a problem that the reflection loss of light caused by the refractive index difference between the protective panel and the air layer, and the refractive index difference between the air layer and the display module, is large, resulting in a deterioration in the image quality of the display.
[0006] Therefore, it has been proposed to improve the image quality of a display by filling the gap between the protective panel and the display module with an adhesive layer. For example, Patent Document 1 discloses an adhesive layer having a shear storage modulus (G') of 1.0×10 at 25° C. and 1 Hz for filling the gap between the protective panel and the display module. 5 The pressure-sensitive adhesive layer has a compressive strength of 0.1 Pa or less and a gel fraction of 40% or more. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2010-97070 A Summary of the Invention [Problem to be solved by the invention]
[0008] In Patent Document 1, the pressure-sensitive adhesive layer is designed to have a low storage modulus at room temperature to improve conformability to uneven surfaces. However, when the storage modulus at room temperature is reduced as described above, the storage modulus at high temperatures is reduced more than necessary, causing problems under durability conditions. For example, air bubbles may be generated near uneven surfaces when exposed to high temperature and high humidity conditions. In addition, conventional pressure-sensitive adhesive layers may cause optical unevenness, such as the area near uneven surfaces appearing distorted in appearance.
[0009] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide an adhesive composition, an adhesive, an adhesive sheet, and a laminate that have excellent step-following properties and can suppress the occurrence of optical unevenness. [Means for solving the problem]
[0010] In order to achieve the above object, first, the present invention provides a polymer comprising a monomer unit represented by the following formula (1): [ka] The present invention provides an adhesive composition comprising a (meth)acrylic acid ester polymer (A) containing an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the following formula (Invention 1):
[0011] In the above invention (Invention 1), by containing the above components, the resulting adhesive exhibits good cohesive strength even without containing a crosslinking agent, and has excellent handleability (for example, workability when using the adhesive sheet). In addition to the cohesive strength, excellent stress relaxation properties are exhibited, and the adhesive has excellent step-following properties from the initial stage to high temperature and high humidity conditions. Furthermore, the excellent stress relaxation properties prevent the occurrence of optical unevenness (optical distortion, etc.). And, since the above adhesive composition does not need to contain a crosslinking agent, no curing period (aging) is required to obtain the adhesive, and the productivity of the adhesive sheet can be improved.
[0012] In the above invention (Invention 1), the (meth)acrylic acid ester polymer (A) preferably contains 0.5 mass % or more and 40 mass % or less of the ethylene carbonate-containing monomer as a monomer unit constituting the polymer (Invention 2).
[0013] In the above inventions (Inventions 1 and 2), the ionic compound (B) is preferably an alkali metal salt (Invention 3).
[0014] In the above inventions (Inventions 1 to 3), it is preferable that the content of the ionic compound (B) in the adhesive composition is 0.1 parts by mass or more and 2 parts by mass or less per 100 parts by mass of the (meth)acrylic acid ester polymer (A) (Invention 4).
[0015] In the above inventions (Inventions 1 to 4), the content of the crosslinking agent in the pressure-sensitive adhesive composition is preferably 0.1 part by mass or less per 100 parts by mass of the (meth)acrylic acid ester polymer (A) (Invention 5).
[0016] Secondly, the present invention provides a pressure-sensitive adhesive (Invention 6) obtained by crosslinking the pressure-sensitive adhesive composition (Inventions 1 to 5).
[0017] Thirdly, the present invention provides an adhesive sheet (Invention 7) comprising at least an adhesive layer, the adhesive layer being made of the adhesive (Invention 6).
[0018] A fourth aspect of the present invention is a pressure-sensitive adhesive sheet including at least a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a strain of 50% or more and 260% or less 1210 seconds after a stress of 7950 Pa is applied to the pressure-sensitive adhesive at 25°C; The maximum relaxation elastic modulus G(t) of the adhesive constituting the adhesive layer is determined according to JIS K7244-1 when the adhesive is subjected to 10% strain. max (MPa), and the maximum relaxation modulus G(t) max The adhesive was subjected to 10% strain until 3757 seconds had elapsed since the measurement, and the minimum relaxation modulus G(t) was determined as the minimum relaxation modulus G(t). min The pressure-sensitive adhesive sheet is characterized in that the relaxation elastic modulus fluctuation value ΔlogG(t), calculated from the following formula (X) (MPa), is 1.2 or more and 2.0 or less (Invention 8). ΔlogG(t)=logG(t) max -logG(t) min …(X)
[0019] In the above inventions (Inventions 7 and 8), the gel fraction of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is preferably 0% or more and 60% or less (Invention 9).
[0020] In the above inventions (Inventions 7 to 9), the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer preferably has a storage modulus (G') at 50° C. of 0.01 MPa or more and 1 MPa or less (Invention 10).
[0021] In the above inventions (Inventions 7 to 10), the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer preferably has a storage modulus (G') at 25° C. of 0.01 MPa or more and 1 MPa or less (Invention 11).
[0022] In the above inventions (Inventions 7 to 11), the adhesive strength of the pressure-sensitive adhesive layer to soda-lime glass is preferably 1 N / 25 mm or more and 100 N / 25 mm or less (Invention 12).
[0023] In the above inventions (Inventions 7 to 12), it is preferable that the adhesive sheet has two release sheets, and the adhesive layer is sandwiched between the release sheets so as to be in contact with the release surfaces of the two release sheets (Invention 13).
[0024] Fifthly, the present invention provides a laminate (Invention 14) comprising one display component, another display component, and an adhesive layer for bonding the one display component and the other display component to each other, characterized in that the adhesive layer is formed from the adhesive layer of the adhesive sheet (Inventions 7 to 13).
[0025] In the above invention (Invention 14), it is preferable that at least one of the one display body component and the other display body component has a step on the surface that is bonded by the pressure-sensitive adhesive layer (Invention 15). Effect of the Invention
[0026] The pressure-sensitive adhesive composition, pressure-sensitive adhesive, pressure-sensitive adhesive sheet and laminate according to the present invention have excellent step conformability and can suppress the occurrence of optical unevenness. [Brief description of the drawings]
[0027] [Figure 1] 1 is a cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a laminate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, an embodiment of the present invention will be described. [Adhesive composition] The adhesive composition according to one embodiment of the present invention (hereinafter sometimes referred to as "adhesive composition P") comprises, as a monomer unit constituting a polymer, a monomer unit represented by the following formula (1): [ka] It is preferable that the composition contains a (meth)acrylic acid ester polymer (A) containing an ethylene carbonate-containing monomer having an ethylene carbonate structure shown in the following formula (1) and an ionic compound (B). In this specification, (meth)acrylic acid means both acrylic acid and methacrylic acid. The same applies to other similar terms. In addition, the term "polymer" also includes the concept of "copolymer."
[0029] Since the (meth)acrylic acid ester polymer (A) is composed of the ethylene carbonate-containing monomer, the adhesive composition P according to the present embodiment contains an ethylene carbonate structure as a side chain of the (meth)acrylic acid ester polymer (A). When the (meth)acrylic acid ester polymer (A) contains an ethylene carbonate structure in the side chain, the interaction between the side chains becomes strong, and the glass transition temperature (Tg) of the (meth)acrylic acid ester polymer (A) becomes relatively high. This increases the cohesive force of the resulting adhesive. In addition, the ethylene carbonate structure contains two carbonyl dipoles. This causes the ethylene carbonate structure as the side chain of the (meth)acrylic acid ester polymer (A) to bond with the ionic compound (B) through interaction to form a pseudo-crosslinked structure. By containing such a crosslinked structure, the resulting adhesive exhibits good cohesive force even without containing a crosslinking agent, and has excellent handleability (for example, workability when using an adhesive sheet). Furthermore, from the viewpoint of the polarity of the ethylene carbonate structure, the adhesive obtained has high adhesive strength, particularly adhesive strength to glass. On the other hand, when a predetermined pressure (and heat) is applied to the adhesive, the crosslinked structure is loosened and excellent stress relaxation properties are exhibited, and for example, when the adhesive has a step or the like on the object to which the adhesive is to be attached, the adhesive easily conforms to the shape of the step or the like. After that, even if the predetermined pressure (and heat) is removed, a pseudo crosslinked structure is formed again while maintaining a state in which the adhesive conforms well to the shape of the step or the like. In such a case, since the stress in the adhesive when conforming to the shape of the step or the like is unlikely to remain, the force of the adhesive to return to the state before conforming can be suppressed to a small value, and the adhesive can maintain a state in which the adhesive conforms well to the shape of the step or the like. Due to these effects, the adhesive sheet obtained using the adhesive has excellent step conformability from the initial stage to high temperature and high humidity. Note that the "initial stage" here does not include the stage immediately after application.In addition, the residual stress of a general adhesive is prominent in the vicinity of a step or the like, and for example, even in the case where the adhesive has excellent step-following ability from the initial stage to high temperature and high humidity (i.e., no bubbles, lifting, or peeling occurs in the vicinity of the step or the like), optical unevenness (optical distortion, etc.) may occur in the vicinity of the step or the like due to the distortion of the adhesive caused by the force of the adhesive returning to the state before the follow. However, the adhesive sheet obtained by using the adhesive obtained from the adhesive composition P according to this embodiment can suppress the force of the adhesive returning to the state before the follow, and therefore has excellent suppression of optical unevenness in the vicinity of the step or the like, and can provide, for example, excellent image quality and appearance of the display. Furthermore, since the adhesive composition according to this embodiment does not need to contain a crosslinking agent, no curing period (aging) is required to obtain the adhesive, and thus the productivity of the adhesive sheet can be improved. In addition, in this specification, "crosslinking" includes not only general crosslinking by covalent bonds, but also pseudo crosslinking by interactions (including, but not limited to, those due to coordinate bonds, ionic bonds, intermolecular forces, etc.).
[0030] (1) Components of the adhesive composition (1-1) (Meth)acrylic acid ester polymer (A) The ethylene carbonate-containing monomer having the ethylene carbonate structure represented by the above formula (1) is not particularly limited as long as it contains an ethylene carbonate structure and is capable of undergoing a polymerization reaction with other monomers constituting the (meth)acrylic acid ester polymer (A).
[0031] A preferred example of the ethylene carbonate-containing monomer is a (meth)acrylic acid ester having a structure in which an organic group having an ethylene carbonate structure and a (meth)acryloyloxy group are bonded. Examples of such (meth)acrylic acid esters include those represented by the following formula (2): [ka] or an acrylic acid ester represented by the following formula (3): [ka] In both formula (2) and formula (3), n represents an integer of 0 or more. Among the (meth)acrylic acid esters represented by the above formulas (2) and (3), (meth)acrylic acid esters in which n is 1 or more are preferred, and (meth)acrylic acid esters in which n is 2 or more are preferred. When n is 1 or more, the ethylene carbonate group as the side chain of the (meth)acrylic acid ester polymer (A) is located at a position relatively far from the main chain, and the probability that the ethylene carbonate structures present in the obtained adhesive overlap each other increases. This causes stacking interaction between the ethylene carbonate structures to work, making it easier to favorably express the mechanical properties (strain amount, relaxation modulus fluctuation value, storage modulus) and adhesive strength described below. In addition, the interaction between the ethylene carbonate structure and the ionic compound (B) is more easily expressed, making it easier to form a pseudo-crosslinked structure, and increasing the cohesive strength. Due to these actions, the obtained adhesive has better step-following ability. In addition, the optical unevenness is suppressed excellently and the handling property is also excellent. The upper limit of the above n is not particularly limited, but from the viewpoint of polymerization, it is preferably 10 or less, more preferably 6 or less, particularly preferably 4 or less, and even more preferably 3 or less. Among them, from the viewpoint of improving the mechanical properties (strain amount, relaxation modulus fluctuation value, storage modulus) and adhesive strength of the obtained adhesive and being more excellent in step followability, (meth)acrylic acid esters with n=2 are preferred, and (2-oxo-1,3-dioxolan-4-yl)methyl methacrylate with n=2 in formula (3) are particularly preferred. The ethylene carbonate-containing monomer may be used alone or in combination of two or more.
[0032] The (meth)acrylic acid ester polymer (A) preferably contains 0.5% by mass or more of the ethylene carbonate-containing monomer as a monomer unit constituting the polymer, more preferably 1% by mass or more, particularly preferably 5% by mass or more, and even more preferably 10% by mass or more. This allows stacking interaction between ethylene carbonate structures to work, and the mechanical properties (strain amount, relaxation modulus fluctuation value, storage modulus) and adhesive strength described below are easily exhibited. In addition, the interaction between the ethylene carbonate structure and the ionic compound (B) is easily exhibited, and a pseudo-crosslinked structure is more easily formed, resulting in high cohesive strength. Due to these actions, the resulting adhesive has better step-following properties. In addition, the adhesive has excellent suppression of optical unevenness and excellent handleability. Furthermore, from the viewpoint of polarity, the adhesive has high adhesive strength, especially adhesive strength to glass.
[0033] On the other hand, the (meth)acrylic acid ester polymer (A) preferably contains the ethylene carbonate-containing monomer as a monomer unit constituting the polymer in an amount of 40% by mass or less, more preferably 30% by mass or less, particularly preferably 25% by mass or less, and even more preferably 20% by mass or less, which makes it easier to satisfy the mechanical properties (strain amount, relaxation modulus fluctuation value, storage modulus) described later, and provides better conformability to uneven surfaces.
[0034] In the present embodiment, the (meth)acrylic acid ester polymer (A) preferably contains a (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer. This allows the resulting adhesive to exhibit good adhesiveness. The alkyl group may be linear or branched.
[0035] From the viewpoint of adhesion, the (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20. Examples of the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20 include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, and stearyl (meth)acrylate.
[0036] Among the above, from the viewpoint of imparting good adhesion, (meth)acrylic acid alkyl esters having an alkyl group with a carbon number of 2 to 12 are more preferred, and (meth)acrylic acid alkyl esters having an alkyl group with a carbon number of 4 to 10 are particularly preferred. Specifically, n-butyl (meth)acrylate is preferred, and n-butyl acrylate is particularly preferred. These may be used alone or in combination of two or more.
[0037] From the viewpoint of imparting good adhesion, the (meth)acrylic acid ester polymer (A) preferably contains 50% by mass or more of (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer, more preferably 60% by mass or more, particularly preferably 70% by mass or more, and even more preferably 80% by mass or more. Also, from the viewpoint of ensuring the content of other monomers (particularly ethylene carbonate-containing monomers), it preferably contains 99.6% by mass or less of (meth)acrylic acid alkyl ester, more preferably 99% by mass or less, particularly preferably 95% by mass or less, and even more preferably 90% by mass or less.
[0038] It is also preferable that the (meth)acrylic acid ester polymer (A) contains a reactive functional group-containing monomer having a reactive functional group in the molecule as a monomer constituting the polymer. By containing a reactive functional group-containing monomer, the interaction between the (meth)acrylic acid ester polymer (A) and the ionic compound (B) is more easily exerted, and a pseudo-crosslinked structure is more easily formed. As a result, the obtained pressure-sensitive adhesive has a high cohesive force, and the mechanical properties (strain amount, relaxation modulus fluctuation value, storage modulus) described later are more easily satisfied, resulting in a more excellent step-following property.
[0039] The reactive functional group-containing monomer preferably includes a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), and a monomer having an amino group in the molecule (amino group-containing monomer). Among these, a hydroxyl group-containing monomer is preferred from the viewpoint of facilitating the formation of the pseudo crosslinked structure. These reactive functional group-containing monomers may be used alone or in combination of two or more.
[0040] Examples of hydroxyl group-containing monomers include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among them, from the viewpoint of facilitating the formation of the pseudo crosslinked structure, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred, and 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate are particularly preferred. These may be used alone or in combination of two or more.
[0041] Examples of the carboxyl group-containing monomer include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, citraconic acid, etc. These may be used alone or in combination of two or more kinds.
[0042] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate, n-butylaminoethyl (meth)acrylate, etc. These may be used alone or in combination of two or more.
[0043] The (meth)acrylic acid ester polymer (A) preferably contains reactive functional group-containing monomers as monomers constituting the polymer in an amount of 0.1% by mass or more as a lower limit, more preferably 0.5% by mass or more, and particularly preferably 1% by mass or more. The (meth)acrylic acid ester polymer (A) preferably contains reactive functional group-containing monomers as monomer units constituting the polymer in an amount of 10% by mass or less as an upper limit, more preferably 8% by mass or less, particularly preferably 6% by mass or less, and even more preferably 3% by mass or less. When the (meth)acrylic acid ester polymer (A) contains reactive functional group-containing monomers as monomer units constituting the polymer in the above range, the pseudo crosslinked structure is more easily formed. This increases the cohesive force of the resulting pressure-sensitive adhesive, making it easier to satisfy the mechanical properties (strain amount, relaxation modulus fluctuation value, storage modulus) described below, and thus providing superior step followability. In addition, the pressure-sensitive adhesive is excellent in suppressing optical unevenness and also has excellent handleability.
[0044] The (meth)acrylic acid ester polymer (A) in this embodiment may further contain other monomers as monomers constituting the polymer. Examples of the other monomers include alicyclic structure-containing (meth)acrylic acid esters such as dicyclopentanyl (meth)acrylate, adamantyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate; alkoxyalkyl (meth)acrylic acid esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; non-crosslinkable acrylamides such as acrylamide and methacrylamide; non-crosslinkable (meth)acrylic acid esters having a tertiary amino group such as N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate; vinyl acetate; and styrene. These may be used alone or in combination of two or more.
[0045] The polymerization mode of the (meth)acrylic acid ester polymer (A) in this embodiment may be a random polymer or a block polymer. The (meth)acrylic acid ester polymer (A) can be obtained by polymerizing each of the above-mentioned monomers by a conventional method. For example, it can be prepared by polymerization using an emulsion polymerization method, a solution polymerization method, a suspension polymerization method, a bulk polymerization method, an aqueous solution polymerization method, or the like. Among them, from the viewpoints of stability during polymerization and ease of handling during use, it is preferable to prepare it by a solution polymerization method carried out in an organic solvent.
[0046] The weight average molecular weight of the (meth)acrylic acid ester polymer (A) is preferably 100,000 or more, more preferably 300,000 or more, particularly preferably 500,000 or more, and even more preferably 650,000 or more. The weight average molecular weight is preferably 2,000,000 or less, more preferably 1,500,000 or less, particularly preferably 1,000,000 or less, and even more preferably 800,000 or less. When the weight average molecular weight of the (meth)acrylic acid ester polymer (A) is within the above range, the resulting adhesive is more likely to satisfy the mechanical properties (strain amount, relaxation modulus fluctuation value, storage modulus) described below, and is more excellent in step followability. In addition, the adhesive is excellent in suppressing optical unevenness and is also excellent in handleability. The weight average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) in terms of standard polystyrene.
[0047] The adhesive composition P according to the present embodiment may contain one type of the above-mentioned (meth)acrylic acid ester polymer (A), or may contain two or more types. The adhesive composition P according to the present embodiment may contain another (meth)acrylic acid ester polymer together with the above-mentioned (meth)acrylic acid ester polymer (A).
[0048] (1-2) Ionic compounds (B) In the present specification, the ionic compound refers to a compound in which a cation and an anion are mainly bound by electrostatic attraction. The ionic compound (B) in the present embodiment may be a liquid (ionic liquid) or a solid (ionic solid) at room temperature.
[0049] Examples of the ionic compound (B) include alkali metal salts, alkaline earth metal salts, nitrogen-containing onium salts, sulfur-containing onium salts, and phosphorus-containing onium salts. Among these, from the viewpoint of easily forming the pseudo-crosslinked structure with the (meth)acrylic acid ester polymer (A), alkali metal salts or alkaline earth metal salts are preferred, and alkali metal salts are particularly preferred. The ionic compound (B) can be used alone or in combination of two or more.
[0050] Specific examples of the alkali metal salt include potassium bis(fluorosulfonyl)imide, lithium bis(fluorosulfonyl)imide, potassium bis(fluoromethanesulfonyl)imide, lithium bis(fluoromethanesulfonyl)imide, potassium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, etc. Among these, lithium bis(trifluoromethanesulfonyl)imide is preferred from the viewpoint of easily forming the pseudo-crosslinked structure.
[0051] The content of the ionic compound (B) in the adhesive composition is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, particularly preferably 0.3 parts by mass or more, and even more preferably 0.4 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content of the ionic compound (B) is preferably 2 parts by mass or less, more preferably 1.5 parts by mass or less, particularly preferably 1 part by mass or less, and even more preferably 0.7 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). When the content of the ionic compound (B) is within the above range, the degree of the pseudo crosslinking becomes appropriate. As a result, the obtained adhesive easily satisfies the mechanical properties (strain amount, relaxation elastic modulus fluctuation value, storage elastic modulus) described later, and has excellent step followability. In addition, the adhesive has excellent suppression of optical unevenness and excellent handleability.
[0052] (1-3) Various additives If desired, various additives that are commonly used in acrylic adhesives, such as a crosslinking agent, a silane coupling agent, an anti-rust agent, an ultraviolet absorber, a tackifier, an antioxidant, a light stabilizer, a softener, a refractive index adjuster, etc., can be added to the adhesive composition P. Note that polymerization solvents and dilution solvents described below are not included in the additives that constitute the adhesive composition P.
[0053] As described above, the adhesive composition P does not require a crosslinking agent because it forms a pseudo-crosslinked structure. This makes aging unnecessary to obtain the adhesive. From this viewpoint, it is preferable that the adhesive composition P does not contain a crosslinking agent.
[0054] However, the adhesive composition P does not exclude those containing a crosslinking agent. When the adhesive composition P contains a crosslinking agent, the content of the crosslinking agent is preferably 0.1 parts by mass or less, more preferably 0.04 parts by mass or less, and particularly preferably 0.01 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). The crosslinking agent referred to here includes crosslinking agents that form covalent bonds with the (meth)acrylic acid ester polymer (A), such as isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and amine-based crosslinking agents.
[0055] (2) Preparation of adhesive composition The adhesive composition P can be prepared by preparing a (meth)acrylic acid ester polymer (A), mixing the obtained (meth)acrylic acid ester polymer (A) with an ionic compound (B), and adding additives, etc., as desired.
[0056] The (meth)acrylic acid ester polymer (A) can be prepared by polymerizing a mixture of monomers constituting the polymer by a normal radical polymerization method. The polymerization of the (meth)acrylic acid ester polymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as desired. However, the present invention is not limited thereto, and the polymerization may be carried out without a solvent. Examples of the polymerization solvent include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, etc., and two or more of them may be used in combination.
[0057] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more of them may be used in combination. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].
[0058] Examples of organic peroxides include benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxyneodecanoate, t-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.
[0059] In the above polymerization step, the weight average molecular weight of the resulting polymer can be adjusted by adding a chain transfer agent such as 2-mercaptoethanol.
[0060] After the (meth)acrylic acid ester polymer (A) is obtained, the ionic compound (B) and, if desired, a dilution solvent and additives are added to the solution of the (meth)acrylic acid ester polymer (A) and mixed thoroughly to obtain a solvent-diluted adhesive composition P (coating solution). When any of the above components is in a solid state or when precipitation occurs when mixed with other components in an undiluted state, the component may be dissolved or diluted alone in a dilution solvent before mixing with other components.
[0061] Examples of the dilution solvent include aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as methylene chloride and ethylene chloride; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; and cellosolve-based solvents such as ethyl cellosolve.
[0062] The concentration and viscosity of the coating solution thus prepared are not particularly limited as long as they are within the range that allows coating, and can be appropriately selected according to the situation. For example, the adhesive composition P is diluted so that the concentration becomes 10 to 60 mass %. In addition, when obtaining the coating solution, the addition of a dilution solvent or the like is not a necessary condition, and if the adhesive composition P has a viscosity that allows coating, it is not necessary to add a dilution solvent. In this case, the adhesive composition P becomes a coating solution in which the polymerization solvent of the (meth)acrylic acid ester polymer (A) itself serves as the dilution solvent.
[0063] [Adhesive] The adhesive of one embodiment of the present invention is obtained from the adhesive composition P of the above-mentioned embodiment, specifically, by crosslinking (pseudo-crosslinking) the above-mentioned adhesive composition P.
[0064] The crosslinking of the pressure-sensitive adhesive composition P can usually be carried out by a heat treatment. This heat treatment can also serve as a drying treatment for volatilizing a diluting solvent and the like from a coating film of the pressure-sensitive adhesive composition P applied to a desired object.
[0065] The heating temperature in the heat treatment is preferably 50 to 150° C., and more preferably 70 to 120° C. The heating time is preferably 10 seconds to 10 minutes, and more preferably 50 seconds to 5 minutes.
[0066] When the adhesive composition P contains a crosslinking agent, it is desirable to provide a curing period after the heat treatment to complete the crosslinking reaction, but the adhesive composition P according to the present embodiment does not need to contain a crosslinking agent, and in that case, no curing period is required, which can improve the productivity of the adhesive sheet.
[0067] [Adhesive sheet] The pressure-sensitive adhesive sheet according to one embodiment of the present invention includes at least a pressure-sensitive adhesive layer, and is preferably a pressure-sensitive adhesive sheet having a release sheet laminated on one or both sides of the pressure-sensitive adhesive layer.
[0068] The adhesive sheet according to the present embodiment is preferably used for bonding one member to another member, and is particularly preferably used when at least one of the one member and the other member has a step on at least the surface on the adhesive layer side.Preferably, the above-mentioned member is a display member, and therefore, the adhesive sheet according to the present embodiment is preferably used for optical applications, but is not limited thereto.
[0069] In the pressure-sensitive adhesive sheet according to one embodiment of the present invention, the pressure-sensitive adhesive layer is made of the pressure-sensitive adhesive described above. The pressure-sensitive adhesive layer or the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer preferably has the physical properties described below.
[0070] In another embodiment of the pressure-sensitive adhesive sheet of the present invention, the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a strain amount of 50% or more and 260% or less 1210 seconds after a stress of 7950 Pa is applied to the pressure-sensitive adhesive at 25° C., and the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a maximum relaxation elastic modulus G(t) measured when the pressure-sensitive adhesive is strained by 10% according to JIS K7244-1. max (MPa), and the maximum relaxation modulus G(t) max The adhesive was subjected to 10% strain until 3757 seconds after the measurement, and the minimum relaxation modulus G(t) was determined as the minimum relaxation modulus G(t). min (MPa), and the relaxation elastic modulus change value ΔlogG(t) calculated from the following formula (X) is preferably 1.2 or more and 2.0 or less. ΔlogG(t)=logG(t) max -logG(t) min …(X)
[0071] The method for measuring the strain amount (%) and the relaxation modulus G(t) is as shown in the test examples described later. The phrase "when a stress of 7950 Pa is applied to the adhesive" refers to the time when the stress reaches 7950 Pa after applying the stress to the adhesive.
[0072] In the pressure-sensitive adhesive sheet according to the present embodiment, the pressure-sensitive adhesive layer is easily deformed and exhibits excellent stress relaxation properties, so that the pressure-sensitive adhesive layer is excellent in step conformability from the initial stage to high temperature and high humidity conditions. In addition, the pressure-sensitive adhesive sheet is excellent in suppressing optical unevenness and in handleability.
[0073] In particular, when the strain amount is 50% or more, when an external force is applied to the pressure-sensitive adhesive layer, a moderate strain is generated and the pressure-sensitive adhesive layer is easily deformed, so that the pressure-sensitive adhesive layer is likely to have excellent step conformability both in the initial stage and after autoclave treatment. In addition, when the strain amount is 50% or more, the stress relaxation rate fluctuation value ΔlogG(t) tends to be large, and it is easy to satisfy the desired range. From this viewpoint, the strain amount is more preferably 100% or more, particularly preferably 150% or more, and even more preferably 180% or more.
[0074] In particular, when the strain amount is 260% or less, the adhesive exhibits high cohesiveness and has excellent step-following properties even under high temperature and high humidity conditions. In addition, the adhesive is less likely to undergo cohesive failure, and the occurrence of adhesive residue when the adhesive sheet is peeled off from the adherend can be suppressed. Furthermore, the resulting adhesive sheet has excellent handleability. From this perspective, the strain amount is more preferably 240% or less, particularly preferably 225% or less, and even more preferably 200% or less.
[0075] On the other hand, when the relaxation elastic modulus fluctuation value ΔlogG(t) is 1.2 or more, the stress relaxation property is excellent. Therefore, after the pressure-sensitive adhesive sheet is applied to the step of the adherend, stress relaxation inside the pressure-sensitive adhesive is likely to proceed, and the residual stress in the vicinity of the step is likely to be relaxed. As a result, even under high temperature and high humidity conditions, the occurrence of lifting or peeling induced by the residual stress when applying to the step is suppressed, and excellent step conformability is exhibited. From this viewpoint, the relaxation elastic modulus fluctuation value ΔlogG(t) is more preferably 1.3 or more, particularly preferably 1.4 or more, and further preferably 1.44 or more.
[0076] In particular, when the relaxation elastic modulus fluctuation value ΔlogG(t) is 2.0 or less, the pressure-sensitive adhesive is likely to exhibit appropriate stress relaxation properties. From this viewpoint, the relaxation elastic modulus fluctuation value ΔlogG(t) is more preferably 1.8 or less, particularly preferably 1.6 or less, and further preferably 1.5 or less.
[0077] The gel fraction of the adhesive constituting the adhesive layer is preferably 0% or more as a lower limit, more preferably 0.4% or more, particularly preferably 0.8% or more, and even more preferably 1.2% or more. The gel fraction is preferably 60% or less as an upper limit, more preferably 40% or less, particularly preferably 20% or less, even more preferably 10% or less, and most preferably 3% or less. When the gel fraction of the adhesive constituting the adhesive layer is in the above range, it becomes easy to adjust the strain amount and the relaxation elastic modulus fluctuation value ΔlogG(t) to the above range. When the gel fraction is 3% or less, the adhesive can be said to be pseudo-crosslinked, and the initial step followability becomes better. The method for measuring the gel fraction of the adhesive is as shown in the test example described later.
[0078] The storage modulus (G') at 25°C of the adhesive constituting the adhesive layer is preferably 0.01 MPa or more as a lower limit, more preferably 0.05 MPa or more, particularly preferably 0.08 MPa or more, and even more preferably 0.1 MPa or more. By setting the lower limit of the storage modulus (G') at 25°C as above, the adhesive obtained is likely to have the above-mentioned strain amount and relaxation modulus fluctuation value ΔlogG(t) within the above-mentioned range, and has better step followability under high temperature and high humidity conditions. In addition, the adhesive is likely to meet the adhesive force described below. The test method for the storage modulus (G') is as shown in the test example described below.
[0079] On the other hand, the storage modulus (G') at 25°C of the adhesive constituting the adhesive layer is preferably 1 MPa or less as an upper limit, more preferably 0.8 MPa or less, particularly preferably 0.5 MPa or less, and even more preferably 0.2 MPa or less. By setting the upper limit of the storage modulus (G') at 25°C as above, the obtained adhesive is likely to satisfy the above-mentioned ranges of the strain amount and relaxation modulus fluctuation value ΔlogG(t) and has better initial step conformability. In addition, it is likely to satisfy the adhesive strength described below.
[0080] The storage modulus (G') at 50°C of the adhesive constituting the adhesive layer is preferably 0.01 MPa or more as a lower limit, more preferably 0.02 MPa or more, particularly preferably 0.03 MPa or more, and even more preferably 0.04 MPa or more. By setting the lower limit of the storage modulus (G') at 50°C as above, the adhesive obtained is likely to have the above-mentioned strain amount and relaxation modulus fluctuation value ΔlogG(t) within the above-mentioned range, and has better step conformability under high temperature and high humidity conditions. In addition, it is likely to have the adhesive strength described below.
[0081] On the other hand, the storage modulus (G') at 50°C of the adhesive constituting the adhesive layer is preferably 1 MPa or less as an upper limit, more preferably 0.5 MPa or less, particularly preferably 0.3 MPa or less, and even more preferably 0.1 MPa or less. By setting the upper limit of the storage modulus (G') at 50°C as above, the obtained adhesive is likely to satisfy the above-mentioned ranges of the strain amount and relaxation modulus fluctuation value ΔlogG(t) and has better initial step conformability, particularly step conformability after lamination by autoclave or the like. In addition, it is likely to satisfy the adhesive force described below.
[0082] The storage modulus (G') at 85°C of the adhesive constituting the adhesive layer is preferably 0.01 MPa or more as a lower limit, particularly preferably 0.015 MPa or more, and more preferably 0.02 MPa or more. By setting the lower limit of the storage modulus (G') at 85°C as above, the adhesive obtained is likely to have the above-mentioned strain amount and relaxation modulus fluctuation value ΔlogG(t) within the above-mentioned range, and has better step conformability under high temperature and high humidity conditions. In addition, it is likely to have the adhesive strength described below.
[0083] On the other hand, the storage modulus (G') at 85°C of the adhesive constituting the adhesive layer is preferably 1 MPa or less as an upper limit, more preferably 0.5 MPa or less, particularly preferably 0.1 MPa or less, and even more preferably 0.03 MPa or less. By setting the upper limit of the storage modulus (G') at 85°C as above, the adhesive obtained is likely to have the above-mentioned strain amount and relaxation modulus fluctuation value ΔlogG(t) within the above-mentioned range, and has better step conformability under high temperature and high humidity conditions. In addition, it is likely to have the adhesive strength described below.
[0084] The adhesive strength of the adhesive sheet according to the present embodiment to soda lime glass is preferably more than 1N / 25mm as a lower limit, more preferably 5N / 25mm or more, particularly preferably 10N / 25mm or more, and even more preferably 20N / 25mm or more. When the lower limit of the adhesive strength is as above, the step conformability under high temperature and high humidity conditions is more excellent. On the other hand, the upper limit of the adhesive strength to the soda lime glass is not particularly limited, but considering the case where reworkability is required, it is preferably 100N / 25mm or less, more preferably 60N / 25mm or less, particularly preferably 40N / 25mm or less, and even more preferably 30N / 25mm or less.
[0085] The adhesive strength of the adhesive sheet 1 according to the present embodiment to alkali-free glass is preferably more than 1N / 25mm as a lower limit, more preferably 5N / 25mm or more, particularly preferably 10N / 25mm or more, and even more preferably 20N / 25mm or more. When the lower limit of the adhesive strength is as above, the step conformability under high temperature and high humidity conditions is more excellent. On the other hand, the upper limit of the adhesive strength to the alkali-free glass is not particularly limited, but considering the case where reworkability is required, it is preferably 100N / 25mm or less, more preferably 60N / 25mm or less, particularly preferably 40N / 25mm or less, and even more preferably 30N / 25mm or less.
[0086] The adhesive strength basically refers to an adhesive strength measured by a 180-degree peeling method in accordance with JIS Z0237:2009, and the specific test method is as shown in the test examples described later.
[0087] The adhesive or adhesive layer having the above physical properties can be preferably obtained by the adhesive composition P described above, but is not limited thereto.
[0088] Here, a specific configuration as an example of the pressure-sensitive adhesive sheet according to the present embodiment is shown in Fig. 1. As shown in Fig. 1, the pressure-sensitive adhesive sheet 1 according to one embodiment is composed of two release sheets 12a, 12b and an active energy ray-curable pressure-sensitive adhesive layer 11 sandwiched between the two release sheets 12a, 12b so as to be in contact with the release surfaces of the two release sheets 12a, 12b. Note that the release surface of the release sheet in this specification refers to a surface of the release sheet that has releasability, and includes both a surface that has been subjected to a release treatment and a surface that exhibits releasability even without being subjected to a release treatment.
[0089] 1. Each component 1-1. Adhesive layer The pressure-sensitive adhesive layer 11 of the pressure-sensitive adhesive sheet 1 according to this embodiment has the composition or physical properties described above.
[0090] The thickness of the adhesive layer 11 in this embodiment (measured according to JIS K7130) is preferably 1 μm or more, more preferably 5 μm or more, particularly preferably 10 μm or more, and even more preferably 20 μm or more. This makes it easier to exert the adhesive force described above, and the step followability is more excellent. In addition, the thickness of the adhesive layer 11 is preferably 100 μm or less, more preferably 75 μm or less, particularly preferably 50 μm or less, and even more preferably 30 μm or less. This can suppress appearance defects such as indentations and dents on the adhesive layer 11. In addition, it is possible to make the laminate (display, etc.) obtained by using the adhesive sheet 1 thinner. The adhesive layer 11 may be formed as a single layer, or may be formed by laminating multiple layers.
[0091] 1-2.Release sheet Release sheets 12a and 12b protect adhesive layer 11 until adhesive sheet 1 is used, and are peeled off when adhesive sheet 1 (adhesive layer 11) is to be used. In adhesive sheet 1 according to this embodiment, one or both of release sheets 12a and 12b are not necessarily required.
[0092] Examples of the release sheets 12a and 12b include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polyethylene naphthalate films, polybutylene terephthalate films, polyurethane films, ethylene vinyl acetate films, ionomer resin films, ethylene-(meth)acrylic acid polymer films, ethylene-(meth)acrylic acid ester polymer films, polystyrene films, polycarbonate films, polyimide films, and fluororesin films. Crosslinked films of these films are also used. Furthermore, laminated films of these films may be used.
[0093] The release surfaces of the release sheets 12a and 12b are preferably subjected to a release treatment. Examples of the release agent used for the release treatment include alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, and wax-based release agents.
[0094] There is no particular limitation on the thickness of the release sheets 12a and 12b, but it is usually about 20 to 150 μm.
[0095] 2. Manufacturing of adhesive sheets In one example of manufacturing the adhesive sheet 1, a coating solution of the adhesive composition P is applied to the release surface of one release sheet 12a (or 12b), a heat treatment is carried out to crosslink the adhesive composition P, and an adhesive layer 11 is formed, and then the release surface of the other release sheet 12b (or 12a) is superimposed on the adhesive layer 11. In this way, the adhesive sheet 1 is obtained. The conditions for the heat treatment are as described above. By using the adhesive composition P to form the adhesive layer 11, the adhesive sheet 1 can be manufactured without aging.
[0096] In another manufacturing example of the adhesive sheet 1, the adhesive composition P is applied to the release surface of one release sheet 12a, and the adhesive composition P is crosslinked by heat treatment to form an adhesive layer, thereby obtaining a release sheet 12a with an adhesive layer. The adhesive composition P is applied to the release surface of the other release sheet 12b, and the adhesive composition P is crosslinked by heat treatment to form an adhesive layer, thereby obtaining a release sheet 12b with an adhesive layer. Then, the release sheet 12a with an adhesive layer and the release sheet 12b with an adhesive layer are bonded together so that both adhesive layers are in contact with each other to obtain the adhesive layer 11. This allows the adhesive sheet 1 to be obtained. According to this manufacturing example, even if the adhesive layer 11 is thick, it is possible to stably manufacture the adhesive sheet.
[0097] The coating solution of the pressure-sensitive adhesive composition P can be applied by, for example, bar coating, knife coating, roll coating, blade coating, die coating, gravure coating, or the like.
[0098] [Laminate] A laminate according to one embodiment of the present invention includes one display member, another display member, and an adhesive layer for bonding the display members together, the adhesive layer being formed from the adhesive layer of the adhesive sheet described above. This laminate is a display member (display panel) or a component thereof.
[0099] At least one of the first display member and the second display member preferably has a step on the surface to be bonded by the pressure-sensitive adhesive layer, and the step is preferably a step caused by a printed layer. The pressure-sensitive adhesive layer has excellent step conformability from the initial stage to high temperature and high humidity conditions, so that even when the laminate is placed under high temperature and high humidity conditions (e.g., 85°C, 85% RH, 96 hours), the occurrence of bubbles, lifting, peeling, etc. near the step is suppressed. In addition, the pressure-sensitive adhesive layer also has excellent suppression of optical unevenness, so that the occurrence of optical unevenness near the step is also suppressed.
[0100] FIG. 2 shows a specific configuration as an example of the laminate according to this embodiment. 2, the laminate 2 according to this embodiment is composed of a first display body component 21, a second display body component 22, and an adhesive layer 11 located therebetween and sandwiched between the first display body component 21 and the second display body component 22. Moreover, in the laminate 2 according to this embodiment, the first display body component 21 has a step on the surface on the adhesive layer 11 side, and specifically, has a step due to the presence or absence of a printed layer 3.
[0101] The laminate 2 may be a member constituting a part of a display such as a liquid crystal (LCD) display, a light emitting diode (LED) display, an organic electroluminescence (organic EL) display, or electronic paper, or may be the display itself. The display may be a touch panel or a flexible display that is repeatedly bent.
[0102] The pressure-sensitive adhesive layer 11 in the laminate 2 is formed from the pressure-sensitive adhesive layer 11 of the pressure-sensitive adhesive sheet 1 described above, and is preferably the pressure-sensitive adhesive layer 11 itself.
[0103] There are no particular limitations on the first display body component 21 and the second display body component 22 as long as they can be adhered to the adhesive layer 11. Furthermore, the first display body component 21 and the second display body component 22 may be made of the same material or different materials.
[0104] The first display member 21 is preferably a protective panel made of a glass plate, a plastic plate, or a laminate containing them. In this case, the printed layer 3 is generally formed in a frame shape on the adhesive layer 11 side of the first display member 21.
[0105] The glass plate is not particularly limited, and examples thereof include chemically strengthened glass, alkali-free glass, quartz glass, soda-lime glass, barium-strontium-containing glass, aluminosilicate glass, lead glass, borosilicate glass, barium borosilicate glass, etc. The thickness of the glass plate is not particularly limited, but is usually 0.1 to 5 mm, and preferably 0.2 to 2 mm.
[0106] The plastic plate is not particularly limited, and examples thereof include an acrylic plate, a polycarbonate plate, etc. The thickness of the plastic plate is not particularly limited, but is usually 0.2 to 5 mm, preferably 0.4 to 3 mm, particularly preferably 0.6 to 2.5 mm, and further preferably 0.8 to 2.1 mm.
[0107] In addition, various functional layers (transparent conductive film, metal layer, silica layer, hard coat layer, anti-glare layer, etc.) may be provided on one or both sides of the above glass plate or plastic plate, or optical members may be laminated thereon. In addition, the transparent conductive film and the metal layer may be patterned.
[0108] The second display component 22 is preferably an optical element to be attached to the first display component 21, a display module (e.g., a liquid crystal (LCD) module, a light emitting diode (LED) module, an organic electroluminescence (OLED) module, etc.), an optical element as part of a display module, or a laminate including a display module.
[0109] Examples of the optical member include a shatterproof film, a polarizing plate (polarizing film), a polarizer, a retardation plate (retardation film), a viewing angle compensation film, a brightness improvement film, a contrast improvement film, a liquid crystal polymer film, a diffusion film, a semi-transmissive reflective film, a transparent conductive film, etc. Examples of the shatterproof film include a hard coat film having a hard coat layer formed on one side of a base film.
[0110] The material constituting the printing layer 3 is not particularly limited, and known materials for printing are used. The lower limit of the thickness of the printing layer 3, i.e., the height of the step, is preferably 3 μm or more, more preferably 5 μm or more, particularly preferably 7 μm or more, and most preferably 10 μm or more. By setting the lower limit as above, it is possible to sufficiently ensure concealment such as making the electrical wiring invisible from the viewer side. In addition, the upper limit is preferably thinner than the thickness of the adhesive layer, and is preferably 80 μm or less, more preferably 50 μm or less, particularly preferably 25 μm or less, and even more preferably 20 μm or less. By setting the upper limit as above, it is possible to prevent deterioration of the step-following ability of the adhesive layer 11 with respect to the printing layer 3. In addition, it is possible to make the obtained laminate 2 thinner.
[0111] To manufacture the laminate 2, for example, one release sheet 12a of the adhesive sheet 1 is peeled off, and the exposed adhesive layer 11 of the adhesive sheet 1 is attached to the surface of the first display member constituting member 21 on which the printed layer 3 is present. At this time, since the adhesive layer 11 has excellent step conformability, the occurrence of gaps or lifting near the steps caused by the printed layer 3 is suppressed.
[0112] Thereafter, the other release sheet 12b is peeled off from the adhesive layer 11 of the adhesive sheet 1, and the exposed adhesive layer 11 of the adhesive sheet 1 is bonded to the second display body component 22 to obtain the laminate 2. As another example, the bonding order of the first display body component 21 and the second display body component 22 may be reversed.
[0113] When the laminate 2 is obtained as described above, autoclave treatment may be performed to adhere the adhesive layer 11 to the first display body component 21 and the second display body component 22. Since the adhesive layer 11 has excellent step conformability, even at this stage, the occurrence of air bubbles, floating, etc. near the steps is suppressed. In addition, since the adhesive layer 11 has excellent optical unevenness suppression properties, the occurrence of optical unevenness near the steps is also suppressed.
[0114] The autoclave treatment may be carried out by a conventional method, and is preferably carried out, for example, at a temperature of 40 to 80° C. and a pressure of 0.3 to 1 MPa for 5 to 60 minutes.
[0115] In the laminate 2, the pressure-sensitive adhesive layer 11 has excellent conformability to steps, so that even when the laminate 2 is placed under high temperature and high humidity conditions (e.g., 85°C, 85% RH, 96 hours), the occurrence of air bubbles, lifting, peeling, and the like near the steps is suppressed. In addition, the pressure-sensitive adhesive layer 11 has excellent suppression of optical unevenness, so that the occurrence of optical unevenness near the steps is also suppressed.
[0116] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention.
[0117] For example, either one or both of the release sheets 12a and 12b in the adhesive sheet 1 may be omitted, and a desired optical member may be laminated in place of the release sheets 12a and / or 12b. The first display body constituting member 21 may not have the printed layer 3 (step), or may have a step other than the printed layer 3. Furthermore, not only the first display body constituting member 21 but also the second display body constituting member 22 may have a step on the adhesive layer 11 side. EXAMPLES
[0118] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0119] Example 1 1. Preparation of (meth)acrylic acid ester polymer (A) 84 parts by mass of n-butyl acrylate, 15 parts by mass of (2-oxo-1,3-dioxolan-4-yl)methyl methacrylate as an ethylene carbonate-containing monomer, and 1 part by mass of 4-hydroxybutyl acrylate were copolymerized by solution polymerization to prepare a (meth)acrylic acid ester polymer (A). The molecular weight of this (meth)acrylic acid ester polymer (A) was measured by the method described below, and found to have a weight average molecular weight (Mw) of 750,000.
[0120] 2. Preparation of adhesive composition 100 parts by mass (solid content equivalent; the same applies below) of the (meth)acrylic acid ester polymer (A) obtained in the above step 1 and 0.5 parts by mass of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) diluted with methyl ethyl ketone as the ionic compound (B) were mixed, thoroughly stirred, and diluted with methyl ethyl ketone to obtain a coating solution of the adhesive composition. The LiTFSI was diluted with methyl ethyl ketone to a solid content concentration of 10% by mass before blending.
[0121] 3. Manufacturing of adhesive sheets The obtained adhesive composition coating solution was applied by a knife coater to the release-treated surface of a heavy-release type release sheet (manufactured by Lintec Corporation, product name "SP-PET382150"), one side of which was a polyethylene terephthalate film treated with a silicone-based release agent. The coating layer was then heated at 90°C for 1 minute to form an adhesive layer.
[0122] Next, the adhesive layer on the heavy release type release sheet obtained above was bonded to a light release type release sheet (manufactured by Lintec Corporation, product name "SP-PET381130"), one side of a polyethylene terephthalate film which had been release-treated with a silicone-based release agent, so that the release-treated surface of the light release type release sheet was in contact with the adhesive layer, to produce an adhesive sheet having an adhesive layer with a thickness of 25 μm, i.e., an adhesive sheet having a configuration of heavy release type release sheet / adhesive layer (thickness: 25 μm) / light release type release sheet.
[0123] The thickness of the adhesive layer is a value measured in accordance with JIS K7130 using a constant pressure thickness measuring device (manufactured by Techclock Corporation, product name "PG-02").
[0124] Here, the formulations (solid content equivalent) of the pressure-sensitive adhesive composition when the (meth)acrylic acid ester polymer (A) is taken as 100 parts by mass (solid content equivalent) are shown in Table 1. The details of the abbreviations and the like shown in Table 1 are as follows. [(Meth)acrylic acid ester polymer (A)] BA: n-butyl acrylate CARBOM: (2-oxo-1,3-dioxolan-4-yl)methyl methacrylate 4HBA: 4-hydroxybutyl acrylate [Ionic compounds (B)] Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) [Crosslinking agent] Trimethylolpropane modified xylylene diisocyanate (manufactured by Soken Chemical Industries, product name "TD-75")
[0125] [Comparative Examples 1 and 3] An adhesive sheet was produced in the same manner as in Example 1, except that the types and ratios of the monomers constituting the (meth)acrylic acid ester polymer (A) and the amount of the ionic compound (B) were changed as shown in Table 1.
[0126] Comparative Example 2 100 parts by mass of the (meth)acrylic acid ester polymer (A) obtained in step 1 of Example 1 and 0.22 parts by mass of trimethylolpropane-modified xylylene diisocyanate (manufactured by Soken Chemical Industries, Ltd., product name "TD-75") as a crosslinking agent were mixed, thoroughly stirred, and diluted with methyl ethyl ketone to obtain a coating solution of an adhesive composition.
[0127] The obtained adhesive composition coating solution was applied by a knife coater to the release-treated surface of a heavy-release type release sheet (manufactured by Lintec Corporation, product name "SP-PET382150"), one side of which was a polyethylene terephthalate film treated with a silicone-based release agent. The coating layer was then heat-treated at 90°C for 1 minute to form a coating layer.
[0128] Next, the coating layer on the heavy release type release sheet obtained above and a light release type release sheet (manufactured by Lintec Corporation, product name "SP-PET381130"), one side of a polyethylene terephthalate film released and treated with a silicone-based release agent, were attached so that the release-treated surface of the light release type release sheet was in contact with the coating layer, and cured for 7 days under conditions of 23°C and 50% RH to produce an adhesive sheet having an adhesive layer with a thickness of 25 μm, i.e., an adhesive sheet having a configuration of heavy release type release sheet / adhesive layer (thickness: 25 μm) / light release type release sheet.
[0129] [Comparative Examples 4 to 5] An adhesive sheet was produced in the same manner as in Comparative Example 2, except that the types and ratios of the monomers constituting the (meth)acrylic acid ester polymer (A) and the amount of the ionic compound (B) were changed as shown in Table 1.
[0130] The weight average molecular weight (Mw) mentioned above is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC) under the following conditions (GPC measurement). <Measurement conditions> GPC measuring device: Tosoh HLC-8020 GPC columns (passed in the following order): Tosoh Corporation TSK guard column HXL-H TSK gel GMHXL (×2) TSK gel G2000HXL Measurement solvent: Tetrahydrofuran ·Measurement temperature: 40℃
[0131] [Test Example 1] (Measurement of gel fraction) The adhesive sheets prepared in the examples and comparative examples were cut to a size of 80 mm x 80 mm, the adhesive layer was wrapped in a polyester mesh (mesh size 200), and the mass was measured using a precision balance. The mass of the mesh alone was subtracted to calculate the mass of the adhesive alone. This mass was designated M1.
[0132] Next, the adhesive wrapped in the polyester mesh was immersed in ethyl acetate at room temperature (23°C) for 24 hours. The adhesive was then removed and air-dried for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, and then dried in an oven at 80°C for 12 hours. After drying, the mass was weighed using a precision balance, and the mass of the adhesive alone was calculated by subtracting the mass of the mesh alone. This mass was designated M2. The gel fraction (%) was expressed as (M2 / M1) x 100. The gel fraction of the adhesive was calculated from this. The results are shown in Table 2.
[0133] [Test Example 2] (Measurement of storage modulus) The pressure-sensitive adhesive layers of the pressure-sensitive adhesive sheets prepared in the Examples and Comparative Examples were laminated in multiple layers to a thickness of 0.8 mm. A cylindrical body with a diameter of 8 mm (height of 0.8 mm) was punched out from the resulting laminate of pressure-sensitive adhesive layers to prepare a sample.
[0134] The dynamic viscoelasticity of the above samples was measured using a viscoelasticity measuring device (manufactured by Anton Paar, product name "MCR302") under the following conditions by a torsional shear method in accordance with JIS K7244-1, and the storage modulus (G') (MPa) was measured at 25°C, 50°C, and 85°C. The results are shown in Table 2. Measurement frequency: 1Hz Measurement temperature range: -20℃~150℃ Heating rate: 3℃ / min
[0135] [Test Example 3] (Measurement of Relaxation Elastic Modulus Fluctuation) The pressure-sensitive adhesive layers of the pressure-sensitive adhesive sheets prepared in the Examples and Comparative Examples were laminated together to form a laminate having a thickness of 0.8 mm. A cylindrical body having a diameter of 8 mm (height of 0.8 mm) was punched out from the resulting laminate of pressure-sensitive adhesive layers to form a sample.
[0136] The above samples were measured for their relaxation modulus G(t) (MPa) in accordance with JIS K7244-1 using a viscoelasticity measuring device (manufactured by Anton Paar, product name "MCR302") under the following conditions, while continuously straining the adhesive by 10%. From the measurement results, the maximum relaxation modulus G(t) max (MPa) and the maximum relaxation modulus G(t) max The minimum relaxation modulus G(t) measured within 3757 seconds after the measurement min (MPa) was derived. Measurement temperature: 25℃ Measurement points: 1000 points (logarithmic plot)
[0137] Obtained maximum relaxation modulus G(t) max (MPa) and minimum relaxation modulus G(t) min From the relaxation elastic modulus (MPa), the relaxation elastic modulus change value ΔlogG(t) was calculated based on the following formula (X). The results are shown in Table 2. ΔlogG(t)=logG(t) max -logG(t) min …(X)
[0138] [Test Example 4] (Measurement of strain) The pressure-sensitive adhesive layers of the pressure-sensitive adhesive sheets prepared in the Examples and Comparative Examples were laminated together to form a laminate having a thickness of 0.2 mm. A rectangular parallelepiped (height 0.2 mm) of 15 mm x 15 mm was punched out from the resulting laminate of pressure-sensitive adhesive layers to prepare a sample.
[0139] A constant stress was continuously applied to the above sample under the following conditions using a viscoelasticity measuring device (manufactured by Anton Paar, product name "MCR302") in accordance with JIS K7244-1, and the strain (%) was measured 1210 seconds after the start of the application of the stress. The results are shown in Table 2. Measurement temperature: 25℃ Measurement points: 321 points Stress: 7950Pa
[0140] [Test Example 5] (Measurement of adhesive strength) The light release type release sheet was peeled off from the adhesive sheet produced in the examples and comparative examples, and the exposed adhesive layer was attached to an easy-adhesion layer of a polyethylene terephthalate (PET) film (manufactured by Toyobo Co., Ltd., product name "PET TA063", thickness: 100 μm) having an easy-adhesion layer, to obtain a laminate of heavy release type release sheet / adhesive layer / PET film. In addition, for Comparative Example 3, a light release type release sheet was not used during the production of the adhesive sheet, and an adhesive sheet consisting of a heavy release type release sheet / adhesive layer (thickness: 25 μm) was produced, and an easy-adhesion layer of a PET film (manufactured by Toyobo Co., Ltd., product name "PET TA063", thickness: 100 μm) having an easy-adhesion layer was attached to the exposed adhesive layer, to obtain a laminate of heavy release type release sheet / adhesive layer / PET film. The laminate obtained as described above was cut into a width of 25 mm and a length of 100 mm.
[0141] The heavy release type release sheet was peeled off from the laminate under an environment of 23°C and 50% RH, and the exposed adhesive layer was attached to the following two types of adherends, and pressurized for 20 minutes at 0.5 MPa and 50°C in an autoclave manufactured by Kurihara Seisakusho Co., Ltd. After that, the laminate was left for 24 hours under conditions of 23°C and 50% RH, and the adhesive strength (N / 25mm) was measured when the laminate of the PET film and the adhesive layer was peeled off from the adherend using a tensile tester (Tensilon manufactured by Orientec Co., Ltd.) under conditions of a peel speed of 300 mm / min and a peel angle of 180 degrees. The measurement was performed under conditions other than those described here in accordance with JIS Z0237:2009. The results are shown in Table 2. In addition, "CF" in the table indicates that cohesive failure occurred in the adhesive layer. <Adherend> Soda lime glass plate (manufactured by Nippon Sheet Glass Co., Ltd., product name "Soda lime glass", thickness: 1.1 mm) -Non-alkali glass plate (manufactured by Nippon Sheet Glass Co., Ltd., product name "Eagle-X", thickness: 1.1 mm)
[0142] [Test Example 6] (Evaluation of handling) When the light release type release sheet was peeled off from the pressure-sensitive adhesive sheets produced in the Examples and Comparative Examples, the handleability (handleability of the pressure-sensitive adhesive sheet) was evaluated based on the following criteria. The results are shown in Table 2. ◯: The light release type release sheet could be easily peeled off without any deformation, stringiness or cohesive failure of the pressure-sensitive adhesive layer during peeling. Δ: The pressure-sensitive adhesive layer deformed during peeling, but was at a level that allowed the light release type release sheet to be peeled off without stringiness or cohesive failure. ×: During peeling, the adhesive layer was significantly deformed, or stringiness or cohesive failure occurred, making it difficult to peel off the light release type release sheet.
[0143] [Test Example 7] (Evaluation of step-following ability) A UV-curable ink (Teikoku Ink Co., Ltd., product name "POS-911 Sumi") was screen-printed in the shape of a picture frame (outer dimensions: 90 mm long x 50 mm wide, 5 mm thick) on the surface of a glass plate (NSG Precision Co., Ltd., product name "Corning Glass Eagle XG", 90 mm long x 50 mm wide x 0.5 mm thick). Then, UV light (80 W / cm 2 The printed ultraviolet-curable ink was cured using a laser printer (two metal halide lamps, lamp height 15 cm, belt speed 10-15 m / min) to produce a stepped glass plate with printed steps (step heights: 5 μm, 10 μm, 15 μm).
[0144] The light release type release sheet was peeled off from the adhesive sheet produced in the examples and comparative examples, and the exposed adhesive layer was attached to the easy adhesion layer of a polyethylene terephthalate (PET) film (manufactured by Toyobo Co., Ltd., product name "PET TA063", thickness: 100 μm) having an easy adhesion layer. Next, the heavy release type release sheet was peeled off to expose the adhesive layer, and using a laminator (manufactured by Fujipla Co., Ltd., product name "LPD3214"), the adhesive layer was laminated on each stepped glass plate so that it covered the entire frame-shaped print, and this was used as a sample. At this stage, the step followability after lamination (immediately after application) was evaluated based on the following criteria. The results are shown in Table 2. <Adjustable to uneven surfaces after lamination> A: No air bubbles or peeling or lifting were observed near the step. B: Air bubbles with a diameter of 0.2 mm or less were observed near the step, but no lifting or peeling was observed. C: Air bubbles, floating, or peeling with a diameter of more than 0.2 mm was observed near the step.
[0145] The sample was then autoclaved for 20 minutes at 50°C and 0.5 MPa, and then left for 24 hours at normal pressure, 23°C, and 50% RH. At this stage, the step conformability after autoclaving (initial step conformability) was evaluated based on the following criteria. The results are shown in Table 2. <Conformity to unevenness after autoclave treatment> A: No air bubbles or peeling or lifting were observed near the step. B: Air bubbles with a diameter of 0.2 mm or less were observed near the step, but no lifting or peeling was observed. C: Air bubbles, floating, or peeling with a diameter of more than 0.2 mm was observed near the step.
[0146] The autoclave-treated sample was then stored for 96 hours under high temperature and high humidity conditions of 85°C and 85% RH (durability test), and then removed to an environment of 23°C and 50% RH. The adhesive layer (especially near the step caused by the printed layer) was visually inspected, and the step conformability after the high temperature and high humidity conditions was evaluated based on the following criteria. The results are shown in Table 2. <Step-following ability after high temperature and humidity conditions> A: No air bubbles or peeling or lifting were observed near the step. B: Air bubbles with a diameter of 0.2 mm or less were observed near the step, but no lifting or peeling was observed. C: Air bubbles with a diameter of more than 0.2 mm or floating / peeling were observed near the step.
[0147] [Test Example 8] (Evaluation of optical unevenness) A UV-curable ink (Teikoku Ink Co., Ltd., product name "POS-911 Sumi") was screen-printed in the shape of a picture frame (outer dimensions: 90 mm long x 50 mm wide, 5 mm thick) on the surface of a glass plate (NSG Precision Co., Ltd., product name "Corning Glass Eagle XG", 90 mm long x 50 mm wide x 0.5 mm thick). Then, UV light (80 W / cm 2 The printed ultraviolet-curable ink was cured using a laser printer (two metal halide lamps, lamp height 15 cm, belt speed 10-15 m / min) to produce a stepped glass plate with printed steps (step height: 15 μm).
[0148] The light release type release sheet was peeled off from the adhesive sheet produced in the examples and comparative examples, and the exposed adhesive layer was attached to the easy adhesion layer of a polyethylene terephthalate (PET) film (manufactured by Toyobo Co., Ltd., product name "PET TA063", thickness: 100 μm) having an easy adhesion layer. Next, the heavy release type release sheet was peeled off to expose the adhesive layer, and using a laminator (manufactured by Fujipla Co., Ltd., product name "LPD3214"), the adhesive layer was laminated on each stepped glass plate so that it covered the entire frame-shaped print. Thereafter, the sheet was autoclaved for 20 minutes under conditions of 50 ° C. and 0.5 MPa, and left at normal pressure, 23 ° C., and 50% RH for 24 hours, and this was used as a sample.
[0149] The above samples were visually inspected near the step caused by the printed layer, and the optical unevenness was evaluated based on the following criteria. The results are shown in Table 2. Note that Comparative Example 2 was not evaluated because the area near the step could not be sufficiently filled after autoclaving. <Presence or absence of optical unevenness> ◯: No optical unevenness was observed near the step. ×: Optical unevenness was observed near the step.
[0150] In addition, since Comparative Example 3 had poor handleability and it was difficult to prepare samples for carrying out Test Examples 2, 3, 4, and 7, Test Examples 2, 3, 4, and 7 were not carried out.
[0151] [Table 1]
[0152] [Table 2]
[0153] As can be seen from Table 2, the pressure-sensitive adhesive sheets produced in the examples had excellent step conformability after autoclave treatment (initial step conformability) and step conformability after high temperature and high humidity conditions, and also had excellent suppression of optical unevenness. Furthermore, the pressure-sensitive adhesive sheets produced in the examples had high adhesive strength and also excellent handling properties. [Industrial Applicability]
[0154] The pressure-sensitive adhesive sheet according to the present invention can be suitably used, for example, for bonding a protective panel having a step to a desired display component. [Explanation of symbols]
[0155] 1...Adhesive sheet 11...Adhesive layer 12a, 12b...Release sheet 2...Laminate 21...First display member 22... Second display body component 3...Printing layer
Claims
1. As a monomer unit constituting the polymer, 【Chemistry 1】 (A) a (meth)acrylic acid ester polymer containing an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the formula: An ionic compound (B); Contains The weight average molecular weight of the (meth)acrylic acid ester polymer (A) is 500,000 or more and 2,000,000 or less, the ionic compound (B) is at least one selected from the group consisting of an alkali metal salt, an alkaline earth metal salt, a nitrogen-containing onium salt, a sulfur-containing onium salt, and a phosphorus-containing onium salt; The content of the ionic compound (B) is 0.1 parts by mass or more and 2 parts by mass or less based on 100 parts by mass of the (meth)acrylic acid ester polymer (A).
1. An adhesive composition comprising:
2. As a monomer unit constituting the polymer, 【Chemistry 2】 (A) a (meth)acrylic acid ester polymer containing an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the formula: An ionic compound (B); Contains The ethylene carbonate-containing monomer is represented by the following formula (2): 【Chemistry 3】 is an acrylic acid ester represented by the formula: the ionic compound (B) is at least one selected from the group consisting of an alkali metal salt, an alkaline earth metal salt, a nitrogen-containing onium salt, a sulfur-containing onium salt, and a phosphorus-containing onium salt; The content of the ionic compound (B) is 0.1 parts by mass or more and 2 parts by mass or less based on 100 parts by mass of the (meth)acrylic acid ester polymer (A).
1. An adhesive composition comprising:
3. As a monomer unit constituting the polymer, 【Chemistry 4】 (A) a (meth)acrylic acid ester polymer containing an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the formula: An ionic compound (B); Contains The ethylene carbonate-containing monomer is represented by the following formula (3): 【Chemistry 5】 A methacrylic acid ester represented by the formula: the ionic compound (B) is at least one selected from the group consisting of an alkali metal salt, an alkaline earth metal salt, a nitrogen-containing onium salt, a sulfur-containing onium salt, and a phosphorus-containing onium salt; The content of the ionic compound (B) is 0.1 parts by mass or more and 2 parts by mass or less based on 100 parts by mass of the (meth)acrylic acid ester polymer (A).
1. An adhesive composition comprising:
4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, characterized in that the (meth)acrylic acid ester polymer (A) contains, as a monomer unit constituting the polymer, 0.5 mass% or more and 40 mass% or less of the ethylene carbonate-containing monomer.
5. The adhesive composition according to any one of claims 1 to 3, characterized in that the ionic compound (B) is an alkali metal salt.
6. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, characterized in that the content of the crosslinking agent in the pressure-sensitive adhesive composition is 0.1 parts by mass or less per 100 parts by mass of the (meth)acrylic acid ester polymer (A).
7. A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition according to any one of claims 1 to 3.
8. A pressure-sensitive adhesive sheet having at least a pressure-sensitive adhesive layer, The pressure-sensitive adhesive layer is made of the pressure-sensitive adhesive according to claim 7. A pressure-sensitive adhesive sheet characterized by:
9. An adhesive sheet having at least an adhesive layer, The pressure-sensitive adhesive layer is As a monomer unit constituting the polymer, 【Chemistry 6】 (A) a (meth)acrylic acid ester polymer containing an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the formula: An ionic compound (B); The adhesive composition comprises a crosslinked adhesive, the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a strain of 50% or more and 260% or less 1210 seconds after a stress of 7950 Pa is applied to the pressure-sensitive adhesive at 25° C.; the maximum relaxation modulus value of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer measured when the pressure-sensitive adhesive is strained by 10% in accordance with JIS K7244-1 is defined as the maximum relaxation modulus G(t)max (MPa), the pressure-sensitive adhesive is continuously strained by 10% until 3757 seconds after the measurement of the maximum relaxation modulus G(t)max, and the minimum relaxation modulus value measured during that time is defined as the minimum relaxation modulus G(t)min (MPa), and the relaxation modulus fluctuation value ΔlogG(t) calculated from the following formula (X) is 1.2 or more and 2.0 or less, the ionic compound (B) is at least one selected from the group consisting of an alkali metal salt, an alkaline earth metal salt, a nitrogen-containing onium salt, a sulfur-containing onium salt, and a phosphorus-containing onium salt; The content of the ionic compound (B) in the pressure-sensitive adhesive composition is 0.1 parts by mass or more and 2 parts by mass or less based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). A pressure-sensitive adhesive sheet characterized by:
10. An adhesive sheet having at least an adhesive layer, The pressure-sensitive adhesive layer is As a monomer unit constituting the polymer, 【Chemistry 7】 (A) a (meth)acrylic acid ester polymer containing an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the formula: An ionic compound (B); The adhesive composition comprises a crosslinked adhesive, the gel fraction of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is 0% or more and 60% or less; the ionic compound (B) is at least one selected from the group consisting of an alkali metal salt, an alkaline earth metal salt, a nitrogen-containing onium salt, a sulfur-containing onium salt, and a phosphorus-containing onium salt; The content of the ionic compound (B) in the pressure-sensitive adhesive composition is 0.1 parts by mass or more and 2 parts by mass or less based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). A pressure-sensitive adhesive sheet characterized by:
11. An adhesive sheet having at least an adhesive layer, The pressure-sensitive adhesive layer is As a monomer unit constituting the polymer, 【Chemistry 8】 (A) a (meth)acrylic acid ester polymer containing an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the formula: An ionic compound (B); The adhesive composition comprises a crosslinked adhesive, the pressure-sensitive adhesive layer has a storage modulus (G') at 50°C of 0.01 MPa or more and 1 MPa or less; the ionic compound (B) is at least one selected from the group consisting of an alkali metal salt, an alkaline earth metal salt, a nitrogen-containing onium salt, a sulfur-containing onium salt, and a phosphorus-containing onium salt; The content of the ionic compound (B) in the pressure-sensitive adhesive composition is 0.1 parts by mass or more and 2 parts by mass or less based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). A pressure-sensitive adhesive sheet characterized by:
12. An adhesive sheet having at least an adhesive layer, The pressure-sensitive adhesive layer is As a monomer unit constituting the polymer, 【Chemistry 9】 (A) a (meth)acrylic acid ester polymer containing an ethylene carbonate-containing monomer having an ethylene carbonate structure represented by the formula: An ionic compound (B); The adhesive composition comprises a crosslinked adhesive, the pressure-sensitive adhesive layer has a storage modulus (G') at 25°C of 0.01 MPa or more and 1 MPa or less; the ionic compound (B) is at least one selected from the group consisting of an alkali metal salt, an alkaline earth metal salt, a nitrogen-containing onium salt, a sulfur-containing onium salt, and a phosphorus-containing onium salt; The content of the ionic compound (B) in the pressure-sensitive adhesive composition is 0.1 parts by mass or more and 2 parts by mass or less based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). A pressure-sensitive adhesive sheet characterized by:
13. The (meth)acrylic acid ester polymer (A) contains, as a monomer unit constituting the polymer, 0.5 mass% or more and 40 mass% or less of the ethylene carbonate-containing monomer. The pressure-sensitive adhesive sheet according to any one of claims 9 to 12.
14. The pressure-sensitive adhesive sheet according to any one of claims 9 to 12, wherein the ionic compound (B) is an alkali metal salt.
15. The pressure-sensitive adhesive sheet according to any one of claims 9 to 12, characterized in that the content of the crosslinking agent in the pressure-sensitive adhesive composition is 0.1 parts by mass or less per 100 parts by mass of the (meth)acrylic acid ester polymer (A).
16. The pressure-sensitive adhesive sheet according to any one of claims 9 to 12, characterized in that the adhesive strength of the pressure-sensitive adhesive layer to soda-lime glass is 1 N / 25 mm or more and 100 N / 25 mm or less.
17. The pressure-sensitive adhesive sheet has two release sheets, The pressure-sensitive adhesive layer is sandwiched between the two release sheets so as to be in contact with the release surfaces of the release sheets. The pressure-sensitive adhesive sheet according to any one of claims 9 to 12.
18. A display component; Other display component parts, an adhesive layer for bonding the first display member and the second display member to each other; A laminate comprising: The pressure-sensitive adhesive layer is formed from the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet according to any one of claims 9 to 12. A laminate comprising:
19. 19. The laminate according to claim 18, wherein at least one of the first display member and the second display member has a step on a surface to be bonded by the pressure-sensitive adhesive layer.
Citation Information
Patent Citations
JP1981501245A
Thermosetting resin composition
JP1992175359A
Water-based curable resin composition
JP1992325539A
Polymerizable aromatic carboxylic acids and aromatic carboxylic acid anhydrides having cyclic carbonate groups, and formulations containing these compounds
JP1998505868A
(METH)acrylic acid copolymer having five-membered cyclic carbonate group and curable resin composition containing the same
JP2005036081A